MAKNA SOSIAL RERAJAHAN SEMARA RATIH - Untung Suhardi; Ida Bagus Putu Eka Suadnyana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Hindu communities in Bali practice religious teachings by carrying out Yadnya ceremonies. One of the yadnya performed by Hindus in Bali is the Manusa Yadnya, which consists of several stages of ceremonies in a person's life, including the Metatah ceremony. The implementation of the Metatah ceremony in Bali has a meaning contained in each of the ingredients, such as the use of Rerajahan Semara Ratih at the Metatah ceremony. Based on the above, there are several problems that are studied in this paper. The theory used to solve the problem is symbol theory, aesthetic theory and value theory. This research is in the form of qualitative, with data collection techniques namely observation, interview and document study. After the data is collected, it is then analyzed with the stages of data reduction, data presentation and (verification) so that valid results are obtained. From the results of the analysis, several conclusions were obtained, namely the form of Rerajahan Semara Ratih consisting of images of Dewa Semara and Dewi Ratih, the sacred scripts of ang, ah and ong kara mertha, materials and tools and the manufacturing process. The religious function of Rerajahan Semara Ratih is as a means of worshiping Dewa Semara and Dewi Ratih in order to give grace to children who carry out the Metatah ceremony for maturity to welcome the Grehasta period.Keywords: Study of Values, Rerajahan Semara Ratih